JUSTIFICATION OF THE CHOICE OF AIR CONDITIONING SYSTEM FOR LOCOMOTIVES CAB - Khrystian, Ye. V.; Tytarenko, I. V. (Science and Transport Progress, 2007)
The existing systems of an air conditioning by mobile machines are considered, the analysis of the strengths and weaknesses is performed. The improved conditioning system for a locomotive cabin is proposed on the basis of regenerative indirect evaporation cooling.